Nations and nationalism - Gellner, Ernest; Breuilly, John, 1946- (Ithaca, N.Y. : Cornell University Press, 2008)
First published in 1983, Nations and Nationalism remains one of the most influential explanations of the emergence of nationalism ever written. This updated edition of Ernest Gellner's now-canonical work includes a new introductory essay from John Breuilly, tracing the way the field has evolved over the past two decades, and a bibliography of...
Definitions: State and nation ; The Nation -- Culture in agrarian society: Power and culture in the agro-literature society ; The state in agrarian society ; The varieties of agrarian rulers -- Industrial society: The society of perpetual growth ; Social genetics ; The age of universal high culture -- The transition to an age of nationalism: A note on the weakness of nationalism ; Wild and garden cultures -- What is a nation?; The course of true nationalism never did run smooth -- Social entropy and equality in industrial society: Obstacles to entropy ; Fissures and barriers ; A diversity of focus -- A typology of nationalisms: The varieties of nationalist experience ; Diaspora nationalism -- The future of nationalism: Industrial culture : one or many? -- Nationalism and ideology: Who is for Nuremberg? ; One nation, one state -- Conclusion: What is not being said ; Summary.
Originally published as hbk.: Malden, MA : Blackwell Pub., c2006.
First printing 1983.
Fifth printing 1993.
"Bibliography of Ernest Gellner's writings on nationalism / Ian Jarvie": (pages 142-147)
Includes bibliographical references (pages [137]-141) and index.
ENH
Trim education.
Donated by Akbar Ali Khan
Keywords: Nationalism; Industrialization; English language